Fatal human poisonings in central Greece: 2000-2003 - Zagelidou, Helen; Leondari, Roubini; Raftopoulos, Vasilios (My University, 2005)
Poisonings in central Greece due to toxic substances are presented for 2000 through 2003. The data concern human deaths, due to poisonings, which were investigated by the Forensic Department of Larissa, in central Greece. This is the first attempt of collecting toxicological data for this specific area of Greece. The number of deaths per year, the sex and age of the deceased, the number of toxicological analyses required and the results are presented. The total number of yearly poisonings did not vary significantly. There was also an increase of deaths due to medical compounds, with stable number of pesticide deaths.
Keywords: Amphetamines; Benzodiazepines; Drugs; Carbon monoxide; Forensic medicine